Next‐Generation DILI Biomarkers: Prioritization of Biomarkers for Qualification and Best Practices for Biospecimen Collection in Drug Development. Issue 2 (14th September 2019) - Roth, Sharin E.; Avigan, Mark I.; Bourdet, David; Brott, David; Church, Rachel; Dash, Ajit; Keller, Douglas; Sherratt, Philip; Watkins, Paul B.; Westcott‐Baker, Lucas; Lentini, Silvia; Merz, Michael; et al.
Abstract : The diagnosis and management of drug‐induced liver injury (DILI) remains a challenge in clinical trials in drug development. The qualification of emerging biomarkers capable of predicting DILI soon after the initiation of treatment, differentiating DILI from underlying liver disease, identifying the causal entity, and assigning appropriate treatment options after DILI is diagnosed are needed. Qualification efforts have been hindered by lack of properly stored and consented biospecimens that are linked to clinical data relevant to a specific context of use. Recommendations are made for biospecimen collection procedures, with the focus on clinical trials, and for specific emerging biomarkers to focus qualification efforts.